KORELASI ANTARA KECERDASAN LOGIS MATEMATIS DENGAN KOMPETENSI INTI PENGETAHUAN MATEMATIKA SISWA KELAS V SD GUGUS LETKOL WISNU KECAMATAN DENPASAR UTARA - Ni Luh Desy Antari (Universitas Pendidikan Ganesha, 2018)
This study aimed to determine the significant correlation between the logical mathematical intelligence with the core competency of knowledge of mathematics students of grade V SD Gugus Letkol Wisnu, North Denpasar, in the Lesson Year 2017/2018. This research is ex post facto research with correlation type. The population of this study is a class V student residing in SD Gugus Letkol Wisnu, North Denpasar Lesson Year 2017/2018 which has a population of 340 people. Determination of the sample used proportional random sampling technique with significant level 5% and obtained the number of samples from the population is 172 people. The data were obtained through results of the essay test of the logical mathematical intellegence and the document recording of the core competency of knowledge of mathematics student. As the test is a normality test data distribution. After all prerequisite tests are met, the statistical analysis used in this next study is hypothesis test using product moment correlation analysis. Based on result of analysis then = 0,472. At the significant levelof 5% with n = 172, then obtained = 0.148. Because >= 0.472> 0.148 it can be interpreted that H₀which reads there is not significant correlation betweenthe logical mathematical intelligence with the core competency of knowledge of mathematics students of grade V SD Gugus Letkol Wisnu, North Denpasar, in the Lesson Year 2017/2018 is rejected and accepted. So it can be concluded that there is a significant correlation between the logical mathematical intelligence with the core competency of knowledge of mathematics students of grade V SD Gugus Letkol Wisnu, North Denpasar, in the Lesson Year 2017/2018, with a positive correlation direction, meaning the higher logical mathematical intelligence then the higher the core competency of knowledge of mathematics students.